Fine-Grained Control for Neighbour Node Anonymity in Opportunistic Mobile Networks - Jaiswal, AS; Welekar, R (International Journal of Computer Sciences and Engineering, 2025)
The major objective of any communication system is to have the messages dispatched to their corresponding terminal. The network topology of DTNs/OMNs is not only highly dynamic, but also exhibits high degree of network partitioning. The maneuverability of the node in delay tolerant network considerably harms the productivity of data forwarding. The proposed approach selects the path according to the feasible number of hops needed to reach the corresponding node. The architecture anonymizes each and every node of the network by giving them fake ids. When a node wants to send its confidential data to the other node then the sender node and receiver node only knows each other’s real id. Here the data is send in the encrypted form which can be decrypted using a key.